AFIKSASI DERIVASIONAL PEMBENTUKAN VERBA DALAM BAHASA JERMAN - , Andung Aris Sayogo, Prof. Dr. I Dewa Putu Wijana, S.U., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study is aimed at describing four main concerns, namely 1) the derivational affixes of German verb, 2) the derivational affixes process of German verb, 3) the morfofonemic system of derivational affixation of German verb, 4) the grammatical meaning of the affixes. This sudy uses a descriptive method. The data are derivational verbs in âGerman_Indonesia Dictionaryâ written by Adolf Heuken, S. J. These data are analyzed by using ultimate constituent analysis technique. The verbs derivations are further analyzed into smaller units by using the ultimate constituent analysis in order to get a clear identification about the forms of affixes, the description of affixation process, the morfofonemic system of the derivational affixation and the grammatical meaning of the affixes. The finding of this study show the following results: 1) the derivational affixes of German verb that can be used in order to create a verb from noun are ein-, nach-, um-, weg-, -ifizieren, -schen, and the derivational affixes of German verb that can be used in order to create a verb from noun and adjective are ab-, an-, auf-, aus-, ent-, er-, vor-, ver-, zer-, be-, -eln, -igen, -ieren, -isieren, 2) there are two kinds of derivational affixation process of German verb, namely nouns and adjectives, 3) the morfofonemic system of derivational affixation of German verb are the appearance of fonems, the change of fonems, the deletion of fonems, the moving of fonems, and the double of fonems, 4) the grammatical meanings of the derivational affixes are âan active actionâ, âdoing activitiesâ, âapurposive actionâ, âa causative actionâ, and âa perspective aspectâ.